1993
DOI: 10.1200/jco.1993.11.8.1482
|View full text |Cite
|
Sign up to set email alerts
|

Myeloablative radiochemotherapy and hematopoietic stem-cell rescue in poor-prognosis Ewing's sarcoma.

Abstract: Myeloblative therapy with hyper-ME +/- C radiochemotherapy can improve the prognosis of multifocal primary and early or multiple relapsing Ewing's sarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
103
1
7

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(113 citation statements)
references
References 9 publications
2
103
1
7
Order By: Relevance
“…Many studies have been conducted to assess the benefit of this megachemotherapy. Some studies suggested an improvement in clinical outcomes, [37][38][39] whereas others did not. 40,41 In the current study, HDC with hematopoietic stem cell rescue failed to improve EFS significantly among high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been conducted to assess the benefit of this megachemotherapy. Some studies suggested an improvement in clinical outcomes, [37][38][39] whereas others did not. 40,41 In the current study, HDC with hematopoietic stem cell rescue failed to improve EFS significantly among high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8][17][18][19][20][21] The outcome of metastatic patients remains dismal, especially for patients with bone and BM involvement. [4][5][6][9][10][11] Rodriguez Galindo et al 23 suggested risk stratification, taking into account simple clinical features, such as age, stage, tumor volume, localization and histological response to chemotherapy, to modulate treatment intensification in different subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…The patient populations enrolled in the published studies were heterogeneous and treated with different conditioning regimens, most of them based on melphalan and/or BU. [9][10][11] This paper reports our experience with HDC based on etoposide, thiotepa and CY (ETC) in poor-prognosis ESFT cases treated at Ospedale Pediatrico Bambino Gesu`over the past 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have addressed the question whether HDC can control primary multifocal ET. [13][14][15][16] The results of these studies are controversial. A carefully controlled study has recently shown that HDC alone may not improve the prognosis of patients with primary multifocal ET.…”
Section: Introductionmentioning
confidence: 99%